Upaya Guru dalam Implementasi Pembelajaran Daring Pada Masa Pandemi Covid-19 di SDN 220 Cinnong - Sidrah Afriani Rachman; Yuni Sulistiawati; Rukayah Rukayah (Universtas Negeri Makassar, 2022)
This research is a descriptive qualitative research that aims to determine the efforts of teachers in implementing online learning during the covid-19 pandemic at SDN 220 Cinnong, Sibulue District, Bone Regency. The subjects in this study were all 6 class teachers at SDN 220 Cinnong. Research data obtained through questionnaires and interviews. Data analysis techniques are data reduction, data display, conclusion drawing/verification. The results of this study reveal a description of the teacher's efforts regarding planning, processes, forms of assessment/evaluation, and the inhibiting and supporting factors for the implementation of online learning during the COVID-19 pandemic at SDN 220 Cinnong, Sibulue District, Bone Regency. The conclusion in this study is that the teacher makes lesson plans in accordance with government recommendations, and the teacher also uses approaches and methods according to the characteristics of students, the method used is the lecture and assignment method, the form of assessment / evaluation is carried out through the whatsapp application. The inhibiting factors are the lack of effectiveness and time efficiency, unstable internet network. While the supporting factors are wifi facilities for teachers and free quotas for students.